The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1528083720960756
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physical characteristics of theyuccafiber

Abstract: Yucca fiber is a natural cellulose fiber that can be extracted from the Yucca plant leaves by retting. The physical properties of the Yucca fiber are extremely sensitive to the retting conditions. This research was designed to study the effects of chemical retting on the structural and properties of this fiber. Chemical retting was done by soaking the Yucca leaf in 10 to 150 g/l sodium hydroxide concentration at 80 to 100 °C for 60 to 240 min. Fiber characteristics such as fineness, tenacity, functional groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The resultant slightly higher fiber's crystallinity in Table 4 was due to the partial removal of non‐crystalline materials such as external lignin and hemicellulose. As a comparison, recent studies reported the fiber crystallinity of agave Yucca ( Asparagus ) up to 66%, depending on the temperature of chemical extraction 32 . In another report, the crystallinity of Yucca ( Aloifolia ) leaves calculated by the Segal method was 69.43% 33 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The resultant slightly higher fiber's crystallinity in Table 4 was due to the partial removal of non‐crystalline materials such as external lignin and hemicellulose. As a comparison, recent studies reported the fiber crystallinity of agave Yucca ( Asparagus ) up to 66%, depending on the temperature of chemical extraction 32 . In another report, the crystallinity of Yucca ( Aloifolia ) leaves calculated by the Segal method was 69.43% 33 .…”
Section: Resultsmentioning
confidence: 95%
“…As a comparison, recent studies reported the fiber crystallinity of agave Yucca (Asparagus) up to 66%, depending on the temperature of chemical extraction. 32 In another report, the crystallinity of Yucca (Aloifolia) leaves calculated by the Segal method was 69.43%. 33 These results indicate that fibers obtained from branches of Yucca (Asparageae) have lower crystallinity than agave-like fibers.…”
Section: Fiber Treatmentsmentioning
confidence: 97%
“…The crystal size of the BPF was 5.22 nm. This smaller crystal size made the BPF more chemically reactive and water-soluble, which might improve the dyeing of these fibres (18) .…”
Section: Results Of Xrd Analysismentioning
confidence: 99%
“…The C = C aromatic ring and C-H vibration of lignin were associated with the peak at 1640 cm -1 , whereas the C-H deformation of cellulose and lignin was associated with the peak at 1384 cm -1 . In addition, a peak at 1034 cm -1 shows the existence of the C-H rocking vibration in cellulose (18) .…”
Section: Results Of Ftir Analysismentioning
confidence: 99%
“…Some fibers, potentially suitable for incorporation into composites, are obtained from the leaves of plants that belong to the former Agavaceae family. This is the case for Agave americana , where natural retting, possibly followed by chemical treatment, proved effective for the production of composites (Hulle et al 2015; Madhu et al 2020; Murugesan et al 2022), and for Yucca filamentosa , where ambitions to obtain possible textile products from short fiber winding were also exposed (Nair et al 2013; Moghaddam and Karimi 2022). As far as the Sansevieria genus is concerned, three types offered fibers that might be used for the production of composites, namely Sansevieria trifasciata (Adeniyi et al 2020), Sansevieria ehrenbergii (Sathishkumar et al 2013), and particularly Sansevieria cylindrica (Sreenivasan et al 2015), in which a larger number of studies on the fibers has been carried out.…”
Section: Introductionmentioning
confidence: 99%